2017
DOI: 10.1016/j.actamat.2017.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and yield strength of SLM-fabricated CM247LC Ni-Superalloy

Abstract: Specimens of Selectively Laser Melted (SLM) CM247LC powder have been characterised using analytical scanning and transmission electron microscopy. In specimens from the bulk, it has been found that longitudinal sections consist mainly of columnar γ grains, containing virtually identically oriented cells, approximately 700 nm in width and length up to hundreds of microns. These cells are separated from adjacent cells and from adjacent grains by γ'/γ eutectic, by high densities of Hf/Ti/Ta/W-rich precipitates an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
71
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(78 citation statements)
references
References 30 publications
6
71
1
Order By: Relevance
“…So far, the Ni-base superalloys applied to SLM are mainly the weldable ones, i.e., IN718 [113,[160][161][162][163][164][165][166][167], IN625 [79,80,168,169], Hastelloy X [170][171][172][173][174], Nimonic 263 [110], which have low additions of both Ti and Al and are less susceptible to strain age cracking. Expansion to the less-weldable Ni-base superalloys has also been attempted, such as IN939 [175], IN100 [176], IN738LC [177][178][179][180][181], CM247LC [114,[182][183][184] and Rene 142 [81]. These researches have shown the great potential for manufacturing complex-geometry critical and functional components for high temperature application via SLM.…”
Section: Materials Manufactured With Slmmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, the Ni-base superalloys applied to SLM are mainly the weldable ones, i.e., IN718 [113,[160][161][162][163][164][165][166][167], IN625 [79,80,168,169], Hastelloy X [170][171][172][173][174], Nimonic 263 [110], which have low additions of both Ti and Al and are less susceptible to strain age cracking. Expansion to the less-weldable Ni-base superalloys has also been attempted, such as IN939 [175], IN100 [176], IN738LC [177][178][179][180][181], CM247LC [114,[182][183][184] and Rene 142 [81]. These researches have shown the great potential for manufacturing complex-geometry critical and functional components for high temperature application via SLM.…”
Section: Materials Manufactured With Slmmentioning
confidence: 99%
“…Correlating the dendrite arm spacing with cooling rate is commonly applied to analyse the solidification behaviours in, for instance, cast and welded materials. However, such correlation by extrapolation might give poor accuracy for the SLM cases [184]. Therefore, the future work on the solidification metallurgy might have to be thought outside the box of traditional solidification scope.…”
Section: Selective Laser Meltingmentioning
confidence: 99%
“…The strains in the substrate are relatively low and homogeneous, but much more inhomogeneous strains are observed in the cladding layers with particularly large strain concentration near the interdendritic regions, because the dislocation movement is greatly retarded by the interdendritic phases, especially nano-sized MC particles. As a consequence, the susceptibility to cracking may get more pronounced due to the difficulty of dislocation movements [43]. The primary HAZ is subjected to a significantly higher strain state, and a clearly decreasing strain gradient from the HAZ/cladding interface to deep inside the substrate is visible.…”
Section: The Driving Force For Crack Initiation and Propagationmentioning
confidence: 99%
“…Metal 3D printing technologies such as laser micro sintering (LMS), selective laser melting (SLM) and electron beam melting (EBM) are capable of manufacturing metal components with complex structures and advanced functionalities 1,2 and have been widely applied in aviation, medical and other high-end elds. [3][4][5] However, the extremely fast conditions during the laser or electron beam melt-forming process oen makes it easy to form crack defects, severely affecting the mechanical properties. A recent study reported that the use of a nano zirconiumbased nucleating agent to assemble alloy powder can effectively inhibit micro-cracks and improve the strength of the alloy.…”
Section: Introductionmentioning
confidence: 99%